Determinan Persepsi Masyarakat terhadap Fungsi Gigi Tiruan di Wilayah Kerja Puskesmas Juai - M. Bahrul Ilmi; Khairul Anam; Erwin Ernadi (Universitas Baiturrahim, 2021)
Dentures have many functions, of course all of these things are to improve the degree of health, but there are many factors that cause people to refuse to use dentures. In the district. Juai still has very few health workers (dentists) so that people are more directing themselves to dental artisans who are identical to dentures. The purpose of this study was to determine the determinants of public perceptions of denture function. This study used an analytic survey method with a cross sectional approach. The sample here is accidental sampling, namely the people in the working area of Puskesmas Juai. The instrument used in this study was a questionnaire / interview sheet containing a list of questions about denture function and a questionnaire regarding public perceptions. The data were then processed and analyzed using the chi square statistical test to test the research hypothesis. The results showed that there was no relationship between denture function variables and other variables such as attention, interest, experience & memory, uniqueness & contrast of dentures. The chance of respondents knowing the function of dentures is 4 times higher for respondents with high attention category, 3 times higher for respondents with interest category, 3 times higher for respondents with remembering category & 1.5 times higher for respondents with unique category. It is advisable to provide information about the benefits, stages of manufacture & other denture functions. As a learning medium, denture information should be improved from both electronic media and family support, especially related health workers such as dentists, dental nurses & dental technicians to maximize their knowledge on the function of dentures in health promotion such as outreach to the public & making electronic media